Implementación de los juegos lúdicos para mejorar el aprendizaje de la química inorgánica y su incidencia en el rendimiento académico en los estudiantes de 1RO de B.G.U de la UECIB ¨RÍO JUBAL¨ en el período 2024 – 2025. - Agualsaca Pagalo, María Cecilia (2025)
This research is entitled ¨Implementation of playful games to improve learning in inorganic chemistry and its impact in academic performance in first – year B.G.U. student at UECIB ¨RÍO JUBAL¨ during the 2024 – 2025 period¨. This study seeks to incorporate new pedagogical strategies to innovate the teaching and learning process. The general objective is to implement playful games to enhance the academic performance of students. The methodology used is both bibliographic and field – based, with a mixed approach and a quiasi – experimental research design, as pre - test and pos – test was applied. The study population consisted of all 10 students in the course. The main findings indicate an improvement in academic performance, as students feel more motivated and show greater interest in the subject. Finally, it is concluded that playful games strengthen Chemistry knowledge, enhance critical thinking, develop cognitive skills, motivate students, improve intra – and interpersonal relationships, and contribute to better academic performance.